Wujudkan Kemandirian Petani Melalui Pemberdayaan Kelompok Tani - Cindy Jufrianda; Solfema Solfema; Lili Dasa Putri (STIKes Ibnu Sina Ajibarang, 2025)
This article discusses efforts to build farmer independence in increasing agricultural productivity through empowering farmer groups. Empowering farmer groups is very important in building farmer independence in increasing agricultural productivity. In addition, through empowering farmer groups, it is also a strategic step in realizing farmers who are more independent, innovative, and able to face all the problems being faced to achieve better and increasing agricultural results. Through empowering farmer groups, farmers are given access to knowledge, supporting technology, skills and training in better farm management for the future. Through farmer groups, they can also form a collaborative forum, where farmers can share experiences and strengthen marketing networks and access to get assistance from the government. With the independence that is built, farmers are expected to be able to increase agricultural productivity sustainably and be able to improve economic welfare.